1996
DOI: 10.1002/(sici)1097-0215(19960410)66:2<225::aid-ijc15>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

β1-integrins dominate cell traffic of leukemic cells in human bone-marrow stroma

Abstract: The major function of bone marrow is growth stimulation and differentiation of hematopoietic stem cells (Dorshkind, 1990). In vitro studies of long-term bone-marrow cultures (LTBMC) have emphasized the essential role of bone-marrow stromal cells in hematopoiesis (Dorshkind, 1990). Colonization of bone-marrow precursor cells is mediated by contacts between adhesion receptors on bone-marrow stromal cells and on precursor hematopoietic cells (Leavesley et al., 1994). These precursor cells interact directly with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Previous study has shown that binding of AML cells to extracellular matrix proteins fibronectin and laminin was predominantly b1-integrin-dependent, but AML cell adhesion to BM fibroblast relies on the simultaneous involvement of b1 and b2 integrins as well as other currently unrecognized ligands. Similar observations have also been made that the role of gap junctions in direct contact interaction of leukemic progenitors with bone marrow stromal cell line resulting in similar biologic effects as described in the current report [20,30]. Inclusion of these references in the discussion will significantly support the current data.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous study has shown that binding of AML cells to extracellular matrix proteins fibronectin and laminin was predominantly b1-integrin-dependent, but AML cell adhesion to BM fibroblast relies on the simultaneous involvement of b1 and b2 integrins as well as other currently unrecognized ligands. Similar observations have also been made that the role of gap junctions in direct contact interaction of leukemic progenitors with bone marrow stromal cell line resulting in similar biologic effects as described in the current report [20,30]. Inclusion of these references in the discussion will significantly support the current data.…”
Section: Discussionsupporting
confidence: 85%
“…After in direct contact with HFCL cells the expression of activated Caspase-3 decreased and the expression of Bcl-2 increased.It was also discovered that the effect by HFCL directly contacted with leukemic cells was more significant than that by transwell group. Since b1 integrin plays an important role in the interaction between bone marrow stromal and leukemic Effects of HFCL on the proliferation, differentiation and apoptosis of acute myeloid leukemia cell lines 159 cells [20], it was indicated that b1 integrin might also attach itself to signal transduction pathways of this inhibition of apoptosis. We analysed the gene profiles differently expressed between HL-60 cells and HL-60 cells in direct contact with HFCL by using Affymetrix GeneChip Human Genome U133 set A.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, VCAM-1 is also selectively expressed by endothelial cells in adult and fetal hematopoietic organs 27 where it mediates the in vitro adherence of normal and leukemic cells. [28][29][30] Furthermore, binding on to bone marrow fibroblasts via integrin ␣4␤1/VCAM-1 supported survival of B cell lineage acute lymphoblastic leukemia (ALL) cells. 31 We speculate, therefore, that the observed germinal center binding of B-CLL cells via integrin ␣4␤1/VCAM-1 might mirror the capacity of these cells to use this ligand pair for their migration and proliferation within the microenvironment of hematopoietic organs.…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups have already explored this field and have shared the evidence that ␣4␤1 and ␣5␤1 integrins dominate the traffic of leukemic cells in human BM stroma. For example, K562 cells, an erythroleukemia control cell line, lack the ␣4 and ␣5 receptors and show the absence of binding to the BM [95]. The same group also proposes fibronectin as a matrix for tumour cell adhesion in the BM stroma.…”
Section: Neoplastic Transformationmentioning
confidence: 99%